PERENCANAAN STRUKTUR GEDUNG SILOAM HOSPITALS MEDAN - Lasmaria Angelina P.; Fitri Aprilliana; Windu Partono; Rudi Yuniarto Adi (Jurnal Karya Teknik Sipil, 2014)
SNI 1726- 2012 has been implemented and used as basic guidance for earthquake-resistant building design. This regulation replaced RSNI 1726- 2002 which is not suitable for Indonesia’s area that always undergoes earthquake. Siloam Hospitals Medan Building was designed by RSNI 1726- 2002. This journal describes the result of Siloam Hospitals Medan Building’s calculation by SNI 1726- 2012. Structural analysis of Siloam Hospitals Medan Building is calculated by SAP2000 software. The outputs are internal forces which are used to calculate the dimension of structure and bar which is needed. This structure uses the method of Special Moment Resisting Frame  which is expected that it has a high ductility due to its location where is in soft soil earthquake risk area.